The challenges affecting entrepreneurial intentions amongst sport management students at a South African University. - Zwane, Bonginkosi Siyethemba (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
The uniqueness of sports, given the spread of entrepreneurship in industries and organizations, has provided dynamic opportunities for entrepreneurs. This study investigates the challenges affecting sport management student entrepreneurial intentions at a South African university. A qualitative, explanatory research design was employed, utilising structured interviews with ten undergraduate sport management students. The data was analysed using thematic analysis through ATLAS.ti software. The results indicate that a significant number of students perceive entrepreneurship as a viable solution to combat the high unemployment rate in the sports industry. Key challenges identified include a lack of entrepreneurial skills, insufficient support from family and peers, and limited access to resources. The study highlights the necessity for universities to integrate entrepreneurial education into their curricula to enhance entrepreneurial mindset and self-efficacy. The findings suggest that addressing these challenges through targeted educational strategies can empower sport management students to pursue entrepreneurial ventures, thereby contributing to their employability and the growth of the sports sector. This will provide room for improvement among tertiary education, government, and subjective norms, such as family, friends, and significant others. The primary focus will be on tertiary institutions to help them identify strategies for addressing sport management students' entrepreneurial intentions.